Computed tomography-based assessment of radiographic progression in spine and sacroiliac joints after pregnancy in women with radiographic axial spondyloarthritis - Lee, Kyung-Ann; Lee, So Yun; Kim, Se Hee; Kim, Hyun-Sook; Kim, Hae-Rim; Lee, Sang-Hoon (Frontiers in Medicine, 2022)
Background: Mechanical stress are one of the pathogenesis of axial spondyloarthritis (axSpA). During pregnancy, the mechanical overload on the spine and pelvis increases due to gravid uterus. We aimed to investigate whether pregnancy affects radiographic progression in patients with radiographic axSpA (r-axSpA) based on computed tomography (CT) evaluations. Materials and Methods: This retrospective study included women with r-axSpA aged 19-49 years who underwent at least two CT evaluations of the whole spine and/or sacroiliac joints (SIJs) at intervals of 2-4 years. To compare radiographic progression after delivery, we classified the patients into two groups: delivery group and controls. The delivery group was restricted to women who had the first CT ~2 years before delivery and the second CT ~2 years after delivery. The CT Syndesmophyte Score (CTSS) (0-522) and SIJ scores (0-40) were used to evaluate spinal syndesmophytes and erosion, joint space narrowing, and sclerosis of the SIJs. Results: A total of 21 women in the delivery group and 38 women in the control group were included. The median (Q1-Q3) CTSS at baseline in the delivery group and controls was 19 (16-23) and 20 (13.25-27.75), and the median progression was 1 (0-3) and 0 (0-1) during the median 2.9-year follow-up, respectively. The median (Q1-Q3) SIJ score at baseline in the delivery group and controls was 13 (8-22) and 11 (6-22), and the median progression was 1.5 (0-3) and 1 (0-2), respectively. Using cut-off 0.5, 52.9% and 61.9% of r-axSpA patients and 39.3% and 44.4% of controls showed progression of whole spine and SIJs, respectively. However, no difference in proportion of spinal and SIJ progression and absolute score changes per time point was observed between two groups. Moreover, the SIJ score changes were comparable according to the delivery method. Conclusions: Pregnancy and delivery do not affect the radiographic progression of the spine and SIJs in women with r-axSpA assessed by CT.